MiR-223-3p attenuates the migration and invasion of NSCLC cells by regulating NLRP3 - Zhu, Shasha; Kong, Xiangbing; Song, Mengru; Chi, Mingyang; Liu, Yitong; Zhang, Peng; Zhang, Qiao; Shang, Pingping; Feng, Feifei (Frontiers in Oncology, 2022)
Lung cancer is the malignant tumor with high invasion and metastasis, which seriously threatens public health. Previous study showed that NLRP3 could promote the occurrence of lung tumors in B(a)P-induced mice. MicroRNAs are closely related to the progression and metastasis of lung cancer by regulating target genes. However, which miRNAs affect the migration and invasion of lung cancer cells through regulating NLRP3 remains poorly defined. In this study, the miRNAs targeting NLRP3 were selected from TargetScan and miRDB database and finally miR-223-3p was chosen due to the consistent expression in both A549 and H520 cells. Then, the migration and invasion of lung cancer cells were detected with miR-223-3p mimic and inhibitor using Transwell assay, at the same time the expression of NLRP3, cleaved caspase-1, IL-1β and IL-18 was determined using Western Blot and immunohistochemistry assay. Our data demonstrated that miR-223-3p was upregulated in both A549 and H520 cells. Furthermore, the migration and invasion of A549 and H520 cells were promoted after inhibitingmiR-223-3p. Besides, the levels of NLRP3, cleaved caspase-1, IL-1β and IL-18 were increased in the two lung cancer cells. And the corresponding results were contrary in miR-223-3p mimic group. Taken together, miR-223-3p attenuates the migration and invasion of NSCLC cells by regulating NLRP3, which provides evidence for the prevention and targeted treatment of NSCLC.